Wong's clinical manual of pediatric nursing - Wilson, David; Hockenberry, Marilyn J. (St.Louis, Missouri : Mosby, Elsevier, 2012)
"This clinical guide is for the care of children and their families, whether in the hospital, clinic, community setting, or home. It includes assessment tools that may be used in practice, nursing care plans for specific disorders, and new information on pediatric pain assessment and management. Evidence-based guidelines are updated and also include patient teaching instructions."--Publisher
unit 1. Assessment -- unit 2. Health promotion -- unit 3. Pain assessment and management -- unit 4. Evidence-based pediatric nursing interventions -- unit 5. Nursing care plans -- unit 6. Reference data
Includes index.
Keywords: PEDIATRIC NURSING -- HANDBOOKS, MANUALS, ETC